Magnetic and Conducting Properties of Composites of Conducting Polymers and Ferrite Nanoparticles - Muñoz Resta, Ignacio (2013)
Composites of ferromagnetic nanoparticles and two conducting polymers (polyethylenedioxythiophene-PEDOT- and polypyrrole-Ppy-) were prepared and characterized. Both syntheses were performed by monomer polymerization in presence of a dispersion of the magnetic nanoparticles, at different monomer: molar ratios. For PPy-composites, both the coercive field and the applied field required to reach the maximum magnetization decrease as the polymer content increases. For PEDOT-composites, the remanence ratio increases as the polymer content increases, indicating the presence of interactions related to the amount of polymer present. Electrical conductivity measurements indicate that, for both types of composites, a high polymer content gives rise to high electrical conductivity. These results indicate that the composite properties can be modulated by varying the polymer identity and the monomer: CoFe2O4 molar ratio.